Gravitation Model and Spatial Interaction: An Application of Geographical Science for Regional Studies - Martha, Sukendra (Forum Geografi, 1996)
Geography as a science describing the inter-relationship between nature and human actions, has a particular applicability values. One of the examples is the use of gravity andÂ  space interaction model approach. This approach applies a formula in which inetraction within space an be known; by multiplying total number of population in two (city) areas and the distances between them. This application is very useful to plan infrastructure, particularly for places having low interaction values.